Emancipation in contradictions: A problematizing search for traces between Critical Bildung Theory and power-analytic critique of subject - Herrmann, Katharina (Momentum Quarterly, 2015)
The concept of emancipation is closely linked with the hope of liberation from restrictive and oppressive settings, with self-empowerment and freedom. As a sign of self-determination, emancipation can also be seen as a target of educational processes in the pedagogical discourse. This paper attempts to irritate the common understanding of emancipation by confronting it with the Critical Bildung Theory by Heinz-Joachim Heydorn and with the analysis of power by Michel Foucault and Judith Butler. This results in a theoretical perspective that challenges emancipatory educational action with respect to its involvement in the reproduction of power while accepting its intention.
Keywords: Emancipation; Critical Bildung Theory; analysis of power; subjectivation